Special Section: Relationships Between Executive Function and Sports / Exercise. Issue 4 (August 2022) - Ball, J.D.
This short article is a commentary on this special section of Perceptual and Motor Skills entitled Relationships between Executive Function and Sports/Exercise. Given the vast executive function research in sports already published, this moment is opportune for highlighting (a) progress to date, (b) research limitations yet to address, and (c) inspirational new findings. The articles that follow illustrate these themes.